Internet use and social trust: empirical analysis based on CGSS2021 - Miao, Juan; Kuang, Junfeng; Yang, Linlin; Chen, Ming; Tian, Xueqing (Frontiers in Sociology, 2025)
The development of the Internet has significantly changed the way people live and interact with each other. Interaction is the foundation for building trust and may therefore also be influenced by the Internet. This study aims to examine the impact of Internet use on different dimensions of social trust, focusing on the roles of perceived fairness and social support, using the latest data from the CGSS from China. The results show that Internet use has a significant negative predictive effect on the level of social trust, and the perception of social fairness plays a fully mediating role in this relationship. That is, Internet use can indirectly reduce people’s level of social trust by reducing their perception of social fairness. Furthermore, the results indicate that social support can moderate people’s perceptions of social fairness and thus mitigate the negative effects of Internet use on social trust. These results suggest that we should raise the profile of the impact of internet use, actively improve people’s perceptions of social fairness to increase their level of social trust, and finally, focus on the positive role of social support, which can reduce the negative impact of internet use.